Effect of transition metal on the physical and hydrogen storage properties of the dynamically stable novel ARhH3 (A = Mg, Ca, and Sr) hydrides for solid-state hydrogen storage application: A DFT and AIMD study - Md. Rabbi Talukder; Md Rasidul Islam (Fuel Processing Technology)
A thorough examination of the physical and hydrogen storage properties of novel ARhH3 (A = Mg, Ca, and Sr) hydrides employs first-principles Density Functional Theory. The mechanical, dynamic, thermodynamic, and phase stability of ARhH3 hydrides were validated by assessing the Born stability criteria, phonon spectra, formation energies, and tolerance factors, respectively. Both the PBE and HSE06 functionals revealed that each of the entitled perovskites exhibits metallic character (Eg = 0 eV), showcasing remarkable conductivity that boosts charge transfer and facilitates the efficient (de)hydrogenation kinetics. Optical functions exhibited great potency in both the visible and UV spectra. The Cauchy pressure, Pugh's, and Poisson's ratios revealed the ductile nature of ARhH3 perovskites. Furthermore, these perovskites exhibit excellent mechanical properties, including Young's modulus of 43.51–127.76 GPa, machinability index of 2.13–11.76, melting temperature of 1483.98–1684.06 K, sound velocity of 1945.51–3452.84 ms−1, and notable anisotropic behavior. The thermal stability of these hydrides was confirmed by the thermodynamic evaluations and AIMD simulations. MgRhH3, CaRhH3, and SrRhH3 demonstrated substantial gravimetric hydrogen storage capacities of 2.34, 2.07, and 1.56 wt%, as well as volumetric storage capacities of 117.65, 103.14, and 93.36 gH2/L, respectively. Interestingly, the hydrogen desorption temperatures for MgRhH3, CaRhH3, and SrRhH3 are recorded at 481 K, 531 K, and 493 K, respectively, enabling them to be highly suitable for practical solid-state hydrogen storage applications.